Remitting Seronegative Symmetrical Synovitis with Pitting Edema (RS3PE): A Case Report - Şebnem Koldaş Doğan,; Birkan Sonel Tur,; Safiye Tuncer,; Bülent Seçkin, (Archives of Rheumatology, 2007)
Remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome is a disease that affects the elderly and has a sudden onset of edema with swelling on the dorsum of the hands, synovitis on the elbows and flexor tendinitis on the fingers. Serologic tests are negative and radiographic joint destruction does not occur. Etiology of RS3PE syndrome is not known but environmental and infectious agents may play a role in its development. Being a benign syndrome responding to low dose corticosteroid and undergoing to remission in one year, RS3PE syndrome can also be associated with diseases like malignance, polimyalgia rheumatica or amiloidosis. Presented below is the case of a 63-year-old female patient with the complaint of swelling, warming and pain in her wrist, ankle and dorsum of the hands which had suddenly started 9 months previously. (Rheumatism 2007; 22: 72-5)